2018
DOI: 10.3390/su10062034
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Energy System with Optimized Storage for Improvement of Sustainability in a Small Town

Abstract: Abstract:With the rise of renewable energy comes significant challenges and benefits. The current studies on the incorporation of renewable-energy policies and energy-storage technologies attempt to address the optimization of hybrid energy systems (HESs). However, there is a gap between the currents needs of HES in small towns for energy independence and the understanding of integrated optimization approaches for employing the technology. The purpose of this research is to determine the technical, systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Both of these strategies make economic dispatch decisions; they choose the most economical way to serve the load at each time step. HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].Many studies throughout the world have used HOMER software to investigate the optimal design of proposed HESs using LF or CC strategies. Halabi et al [28], Ansong et al [29], Sigarchian et al [30], Rezzouk and Mellit [31], and Madziga et al [32] used the LF strategy to analyze the performance of suggested HESs to find the optimal configurations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these strategies make economic dispatch decisions; they choose the most economical way to serve the load at each time step. HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].Many studies throughout the world have used HOMER software to investigate the optimal design of proposed HESs using LF or CC strategies. Halabi et al [28], Ansong et al [29], Sigarchian et al [30], Rezzouk and Mellit [31], and Madziga et al [32] used the LF strategy to analyze the performance of suggested HESs to find the optimal configurations.…”
mentioning
confidence: 99%
“…Both of these strategies make economic dispatch decisions; they choose the most economical way to serve the load at each time step. HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].…”
mentioning
confidence: 99%
“…Conversely, other studies only evaluate certain components [6,14,16,17], while others do not develop an exhaustive analysis of the Life Cycle Costs (LCC), emissions, and/or primary energy-consumption [3,4,6], which will be analyzed in detail in the present study. Also, for instance, the authors in reference [18] determine the technical, systematic, and financial requirements needed to allow a city or community to become independent of the utilization of traditional energy sources, using hybrid energy-systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that the proposed multi-objective PSO could be validated for multi variable EMS of a factory. The optimal power control strategy for a standalone microgrid was developed and presented in [20] where optimized gains of a proportional-integrator controller of inverter-based DGs using hybrid big bang-big crunch (BB-BC) algorithm were found.With the aim of adjusting microgrid generation to energy demand, numerous technical studies have been carried out to improve energy management with penetration of renewable energy sources combined with energy storage devices in microgrids [21][22][23][24][25]. Alvarez et al [26] conducted an optimization of micro sources in a DG microgrid in terms of emission and fuel consumption costs.…”
mentioning
confidence: 99%
“…With the aim of adjusting microgrid generation to energy demand, numerous technical studies have been carried out to improve energy management with penetration of renewable energy sources combined with energy storage devices in microgrids [21][22][23][24][25]. Alvarez et al [26] conducted an optimization of micro sources in a DG microgrid in terms of emission and fuel consumption costs.…”
mentioning
confidence: 99%